Biliary complications after liver transplantation: Assessment with MR cholangiopancreatography and MR imaging at 3T device. Issue 106 (September 2018) - Boraschi, Piero; Donati, Francescamaria; Pacciardi, Federica; Ghinolfi, Davide; Falaschi, Fabio
Highlights: Biliary complications (BCs) after liver transplant represent important causes of morbidity and graft dysfunction. MR is actually the preferred non-invasive imaging modality to identify post-transplant BCs. 3 T MRCP and MRI can predict post-transplant BCs in at least 95%, and exclude them in 99% of cases. MRCP and MRI at 3 T device are extremely reliable for detecting BCs in liver transplant recipients. 3 T MRCP and MRI should be recommended before any invasive diagnostic procedure. Abstract: Purpose: Our study was aimed to assess the diagnostic value of MR cholangiopancreatography (MRCP) and MR imaging at 3 T device when evaluating biliary adverse events after liver transplantation. Materials and methods: A series of 384 MR examinations in 232 liver transplant subjects with suspected biliary complications (impaired liver function tests and/or biliary abnormalities on ultrasound) were performed at 3 T device (GE-DISCOVERY MR750; GE Healthcare). After the acquisition of axial 3D dual-echo T1-weighted images and T2-weighted sequences (propeller and SS-FSE), MRCP was performed through coronal thin-slab 3D-FRFSE and coronal oblique thick-slab SSFSE T2w sequences. DW-MRI of the liver was performed using an axial spin-echo echo-planar sequence with multiple b values (150, 500, 1000, 1500 s/mm 2 ) in all diffusion directions. Contrast-enhanced MRCP was performed in 25/232 patients. All MR images were blindly evaluated by two experienced abdominal radiologists in consensus to determine the presence of biliary complications, whose final diagnosis was based on direct cholangiography, surgery and integrating clinical follow-up with ultrasound and/or MRI findings. Results: In 113 patients no biliary abnormality was observed. The remaining 119 subjects were affected by one or more of the following complications: non-anastomotic strictures including typical ischemic-type biliary lesions (n = 67), anastomotic strictures (n = 34), ampullary dysfunction (n = 4), anastomotic leakage (n = 4), stones, sludge and casts (n = 65), vanishing bile duct (n = 1). The sensitivity, specificity, PPV, NPV and diagnostic accuracy of the reviewers for the detection of all types of biliary complications were 99%, 96%, 95%, 99% and 97%, respectively. Conclusion: MR cholangiopancreatography and MR imaging at 3 T device are extremely reliable for detecting biliary complications after liver transplantation.